2011
DOI: 10.1097/inf.0b013e31822940a8
|View full text |Cite
|
Sign up to set email alerts
|

Central Venous Catheter-related Blood Stream Infections in Children Undergoing Hematopoietic Stem Cell Transplant for Primary Immunodeficiency and Other Nonmalignant Disorders

Abstract: A single-center experience of catheter-related blood stream infections in children undergoing hematopoietic stem cell transplant for primary immunodeficiency is described. The rate of definite central venous catheter infections was 5.31/1000 line days. Staphylococcus epidermidis was the most commonly identified organism. Teicoplanin resistance occurred in 17% of S. epidermidis infections. The central catheter was removed in 21% of infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…It might be suggested that CVC may be changed in 7-10 day intervals, with the need for further studies. Cole et al 25 reported the prevalence of CLABSI in children whose stem cells were transplanted. They had found 5.3/1.000 central-line days and Staphylococcus epidermidis was the most commonly identified organism.…”
Section: Discussionmentioning
confidence: 99%
“…It might be suggested that CVC may be changed in 7-10 day intervals, with the need for further studies. Cole et al 25 reported the prevalence of CLABSI in children whose stem cells were transplanted. They had found 5.3/1.000 central-line days and Staphylococcus epidermidis was the most commonly identified organism.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus , enteric gram-negative bacilli and Candida are less frequent but potentially more severe pathogens. Coagulase-negative Staphylococcus species ( S. epidermidis in particular) were the most common (>50%) pathogens identified from 146 episodes of bacteremia in 64 children with primary immunodeficiencies undergoing HSCT in Great North Children’s Hospital, whereas Enterococcus species, gram-negative organisms, and Candida were isolated only in few cases each ( 30 ). Most (80%) episodes were successfully treated with appropriate systemic and antibiotic locks; CVC was removed in 12 patients, and the only death resulted from overwhelming C. albicans infections despite CVC removal ( 30 ).…”
Section: Possible Risk Factors For Severe Infection and Deathmentioning
confidence: 99%
“…Coagulase-negative Staphylococcus species ( S. epidermidis in particular) were the most common (>50%) pathogens identified from 146 episodes of bacteremia in 64 children with primary immunodeficiencies undergoing HSCT in Great North Children’s Hospital, whereas Enterococcus species, gram-negative organisms, and Candida were isolated only in few cases each ( 30 ). Most (80%) episodes were successfully treated with appropriate systemic and antibiotic locks; CVC was removed in 12 patients, and the only death resulted from overwhelming C. albicans infections despite CVC removal ( 30 ). Contrary to that study, severe and life-threatening CVC-related sepsis caused by S. epidermidis has been reported in a significant percentage of children with systemic vasculitis treated with infliximab and combined immunosuppressive and/or antiinflammatory therapies ( 31 ).…”
Section: Possible Risk Factors For Severe Infection and Deathmentioning
confidence: 99%
“…Another study revealed that incidence was 4.1 per 1.000 central linedays in third world countries [4]. Children with haemopoietic stem cell transplantation, prevalence of CLABSI was 5.3 per 1000 central-line days and most commonly identified organism was Staphylococcus epidermidis [5].…”
Section: Introductionmentioning
confidence: 99%